1996
DOI: 10.1159/000239472
|View full text |Cite
|
Sign up to set email alerts
|

Cotrifazid – An Agent against Malaria

Abstract: Following the brief information on a new malaria treatment with the fixed multiple combination Cotrifazid (rifampicin + isoniazid + sulfamethoxazole + trimethoprim) in Chemotherapy [1995;41:396–398], very good results are reported for the treatment of 61 patients with various forms of malaria. The tolerance was found to be good. Some relevant fundamental considerations (chemoresistance, synergism/antagonism, fixed multiple combination, switching from monotherapy to combination therapy) and the implementation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…A putative prokaryote-like RNA polymerase in P. falciparum has been suggested as one possible target of rifampin (10). A fixed combination of rifampin, co-trimoxazole, and isoniazid was found to be highly effective for the treatment of malaria (9,15). Rifampin was found to be more active after prolonged exposure, in contrast to the results of Divo et al (6).…”
Section: Discussionmentioning
confidence: 97%
“…A putative prokaryote-like RNA polymerase in P. falciparum has been suggested as one possible target of rifampin (10). A fixed combination of rifampin, co-trimoxazole, and isoniazid was found to be highly effective for the treatment of malaria (9,15). Rifampin was found to be more active after prolonged exposure, in contrast to the results of Divo et al (6).…”
Section: Discussionmentioning
confidence: 97%
“…The reasons for use of CF in the treatment of malaria tropica was based exclusively on empiric data reported in 1995/1996 [5,6]. These investigators reported previously for CF positive therapeutic results in tuberculosis, leprosy and chronic Salmonella sp.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators reported previously for CF positive therapeutic results in tuberculosis, leprosy and chronic Salmonella sp. carriers [6]; they postulated a 'synergism' between CF components [19] and stressed the need for a fixed combination, particularly for low-income countries [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medizinisches-diagnostisches Institut, Fatol Arzneimittel GmbH, Schiffweiler, Deutschland A fixed combination of rifampicin (RIF) + isoniazid (INH) + cotrimoxazolc (SXT) (Cotrifazid™) was suggested by Freerkscn et al [1,2] in this journal as a possible alternative for Plasmodium falci parum-provoked malaria. In this connection, a frequently raised ar gument against the use of Cotrifa zid on a broad scale, particularly in high TB prevalence countries, is the assumed possibility of selecting for RIF-rcsistant strains of tubercle bacilli, particularly in regions with possibly high INH drug resistance of Mycobacterium tuberculosis.…”
mentioning
confidence: 99%